Faktor-Faktor yang Berhubungan dengan Self Management pada Pasien DM Tipe II (Journal of Telenursing (JOTING), 2019)
This study aims to identify the factors associated with self-management of type II DM patients in Kendari City. The study design was cross sectional. The results showed a significant relationship between DM knowledge, self-efficacy, family support, motivation and emotional aspects with self management (p